Active Learning In American History Class - Brill, Janice (Teaching History: A Journal of Methods, 1996)
Lost in the vast recesses of dates and names, battles and economic forces, my American history class struggled to choose correctly from among a dizzying number of a-bc-d "pick-a-winner" multiple-choice questions. Where, I asked myself, is the joy of history? Where is the human experience that makes history speak to those who will hear? On a more practical level I asked myself how much of this content was actually acquired? What would be remembered in a few years? I found myself saying too often, "Imagine yourself … how would you feel?" In the end I asked myself, "Why not let them feel, in so far as the limits of time and the classroom will allow?" Why not? My classes have always been regular classes with mainstreamed students. When I began teaching American histay, it was a required 9th grade class, but now it is required of I 0th graders. My class sizes have ranged from 15-25 students. I have found these activities to be especially effective for those students who were not highly motivated in history class.